HORMONES CHANGES TO STRESS - Kadir, Akmarawita (Universitas Wijaya Kusuma Surabaya, 2010)
Various stimuli both physical, chemical, psychological, or psychosocial disorderspose a threat to the homeostasis of the body system can trigger the stress response. Various stressors can cause a variety of specific responses to specific stressor, but in addition to specific responses, all stressors also cause a general response to the same effect whatever itsÂ type of stressor.